Efeitos preventivos do exercício resistido na expressão de proteínas envolvidas na atrofia muscular em ratos tratados com dexametasona - Macedo, Anderson Geremias (Universidade Federal de São Carlos, 2013)
Dexamethasone (Dexa) has been widely used as anti-inflammatory and anti-allergic treatment, however, its chronic use provokes peripheral insulin resistance, hypertension, weight loss and muscle atrophy. Low intensity aerobic training has been indicated for prevention and treatment of diabetes, hypertension and metabolic syndrome, however, its effects on muscle atrophy are still uncertain. Muscle atrophy may be determined by an imbalance between atrophic (FOXO3a, atrogin-1, Murf-1) and hypertrophic (AKT, mTOR) proteins, but almost nothing is known about the effects of Dexa on these proteins. Resistance training (RT) has been recommended for treatment of pathologies which involves muscle atrophy, however little is known about the effects of low intensity RT on the muscle atrophy induced by Dexa. This study investigated whether low intensity RT, performed before and concomitant with Dexa treatment could prevent and / or attenuate muscle atrophy induced by Dexa. Also, it examined the role of proteins that control muscle homeostasis in this response. Forty-eight rats were allocated into 4 groups: sedentary control (SC), sedentary and treated with Dexa (SD), trained control (TC) and trained and treated with Dexa (TD). After an adaptation period, the rats underwent to an resistance exercise protocol (ladder,60% maximal loading, 5 days / week, 70 days) or kept sedentary. During the last 10 days, the rats were treated with Dexa (0.5 mg / kg of bodyweight per day, i.p.). Fasting glycemia was measured before and after exercise training and treatment periods. Bodyweight (BW) was measured weekly before treatment and daily during drug treatment. The tibialis anterior (TA), flexor hallucis longus (FHL) and soleus muscles were removed and homogenized. Protein production of AKT, mTOR, FOXO3a, atrogin-1 and Murf-1 was analyzed in the muscles. Two-way ANOVA with Tukey post-hoc were used (p<0.05). Dexa treatment increased glycemia by 46%, reduced BW by 19% and food intake by 45% in sedentary animals. The RT, that was effective to increase physical capacity of the rats (+118%) prevented the increase in glycemia, but did not avoid the BW reduction. Dexa provoked TA muscle atrophy (-21%), which was determined by reduction of AKT (-29%) and increase of Murf-1 (+25%). RT attenuated the increased the Murf-1 protein production (-37%), however it did not avoid TA muscle atrophy. In the FHL, it was observed muscle atrophy (-28%) determined by reduction of AKT (-27%) and increase of Murf-1 (+55%). RT increased mTOR in TC (+36%) and TD (+72%) groups and also reduced atrogin-1 protein production in TD, which contributed to attenuate FHL muscle atrophy. Soleus muscle was not altered neither by training nor treatment. These data together suggest that low intensity RT was effective in attenuating FHL muscle atrophy due to a combination of increase in hypertrophic and decrease in atrophic protein production.
Keywords: Fisiologia; Dexametasona; Músculo esquelético; Treinamento resistido; Atrofia muscular; Hipertrofia muscular; Resistance training; Atrophic protein; Hypertrophic proteins; Skeletal muscle; Glucocorticoids; CIENCIAS BIOLOGICAS::FISIOLOGIA